India's Trade Relations with SAARC Countries in the Pre and Post SAFTA Periods : An Evaluation of Trade Flows by Using Multiple Regression Model - Singh, Raj Kumar; Singh, Balbir; Chauhan, Diksha (Arthshastra Indian Journal of Economics & Research, 2018)
International trade is an integral part of sustainable economic development of the nation. To foster international trade, the role of regional economic integration has become a significant feature of economic development. Many countries of the world have moved to regional economic integration with the twin objectives to promote economic development and standard of living of citizens. The significance of higher level of economic integration motivated the SAARC countries to sign free trade agreement in 2004. The study sought to examine India's trade potential with SAARC countries during the pre and post SAFTA periods. An annual time series panel data pertaining to SAARC countries from 1990-91 to 2016-2017 was used and transformed into natural logarithm form to reduce the impact of multicollinearity and to make the data comparable. To check the stationarity of the data, Augmented Dickey Fuller and Phillips - Perron tests were applied. Descriptive statistics, ANOVA, and post-hoc tests were used to analyze India's trade with SAARC countries in the pre and post SAFTA periods. Furthermore, the OLS multiple regression model was used to analyze the impact of independent variables on India's trade with SAARC countries.